2021
DOI: 10.1002/cncy.22421
|View full text |Cite
|
Sign up to set email alerts
|

Aptima HPV messenger RNA testing and histopathologic follow‐up in women with HSIL cytology: A study emphasizing additional review of HPV‐negative cases

Abstract: Background High‐risk human papillomavirus (hrHPV) messenger RNA (mRNA) testing, the Food and Drug Administration–approved testing platform since 2013, has been increasing as a cervical screening alternative to hrHPV DNA testing methods. This study reports the largest routine clinical follow‐up study reported to date of hrHPV mRNA cotesting and histopathologic follow‐up results for women with high‐grade squamous intraepithelial lesion (HSIL) cytology results. Methods HSIL Papanicolaou test results for women cot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Another study by Li et al 12 using the Aptima hrHPV test of 951 patients with HSIL paps showed 46 (4.8%) negative for hrHPV. Of these cases, 15 of 35 (42.9%) had HSIL (CIN2/3) or worse on tissue follow‐up, with one invasive SCC.…”
Section: Discussionmentioning
confidence: 95%
“…Another study by Li et al 12 using the Aptima hrHPV test of 951 patients with HSIL paps showed 46 (4.8%) negative for hrHPV. Of these cases, 15 of 35 (42.9%) had HSIL (CIN2/3) or worse on tissue follow‐up, with one invasive SCC.…”
Section: Discussionmentioning
confidence: 95%
“…A study conducted in Shanghai, a region with a similar economic status to our study population, showed that 71.5% of patients with HSIL cytology were diagnosed with CIN2+ lesions, including 3.2% with invasive squamous cell carcinoma (SCC) 23 . Additionally, they conducted another study revealing a CIN2+ rate of 76.8% in hrHPV mRNA-positive cases 15 . Similarly, our study observed a CIN2+ rate of 66.1% in hrHPV mRNA-positive cases.…”
Section: Discussionmentioning
confidence: 99%
“…While most cervical cytology abnormalities are not severe and will not develop into cancer or its precursors, high-grade cervical cytology abnormalities, most of which were positive for hrHPV, have a higher risk of precancerous and cancerous cervical lesions 14 , and these patients often undergo immediate treatment 6 . However, different genotypes of hrHPV carry different risks of developing high-grade lesions 15 . In our previous studies, we demonstrated the benefit of risk-stratifying patients with NILM and ASC-US cytology based on hrHPV genotype for optimizing patient management 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%